King Abdullah Economic City: Engineering Saudi Arabia's post-oil future. (June 2015) - Moser, Sarah; Swain, Marian; Alkhabbaz, Mohammed H.
Highlights: We examine Saudi Arabia's plans to build four new master-planned 'economic cities'. We critically examine Saudi city-centric economic development strategies. KAEC provides insights into strategies to diversify economies away from oil. We analyze challenges relating to social exclusivity, identity, and governance. Abstract: King Abdullah Economic City (KAEC) is a 100 billion master-planned city under construction along Saudi Arabia's Red Sea coast. As part of a quartet of new planned 'economic' cities in the desert kingdom, the city's goal is to provide 1 million jobs for the kingdom's rapidly growing, youthful population and to diversify the Saudi economy away from the oil industry. The city is illustrative of a recent trend of mega-projects on the Arabian Peninsula and the Gulf designed for a post-oil era and fits into broader global trends of economic development strategies. Designed to accommodate 2 million people, KAEC aims to be a global logistics and manufacturing hub that will feature an education zone, 'industrial valley', business district, resort area, sea port, and residential areas for various income brackets. Conceptualized as a modern, international, and socially progressive city, KAEC represents a departure from current Saudi social values and governance and a shift in the ruling elite's priorities. In this paper we examine how the Saudi state seeks to re-invent itself through the construction of new cities and the recent pivot towards economic liberalism. We position the national and international ambitions manifested in KAEC within broader transnational trends in entrepreneurial urbanism and new master-planned cities. Though KAEC is still in the early construction phase, this paper offers a preliminary analysis of the master plan and potential challenges relating to governance.